Orthodoxy or heresy? The dilemma of teachers in front of the institutional fact (Praxis Educativa, 2012)
This article studies the nature of the institutional phenomenon and the relationship between the sociocultural reality and the organizational field. It tries to understand how the institution can impact in some actors in the organizational university space and the way in which a critical perception can contribute to understand the tension between rules and transformations. In that sense, it analizes a subject from the Language Department at the National University of Mar del Plata and some suffering indicators in its members. Discourse analysis of interviews to teachers have been contrasted with other data in a multidirectional approach to understand sociopsychological processes.
Keywords: rules transformations; socio cultural reality; organization